Aphrodisiac Food Ingredients from the Twelve Thai Ancient Formulary Books of Police Captain Bhiam Bunyachot - Jayathavaj, Vadhana; Chuensumran, Ubol (Journal of Food Health and Bioenvironmental Science, 2023)
An aphrodisiac is defined as any food or drug that arouses the sexual instinct, induces venereal desire and increases pleasure and performance. There are many commercial advertisements related to herbal supplements that claim to have an aphrodisiac property. But the claims almost always come from the long-standing belief or traditional wisdom (Chinese or Ayurveda) with no scientific support. To support “food is medicine”, the aphrodisiac herbs from Thai ancient drugs were explored from private formulary books. The properties of aphrodisiac formulas in the formulary texts were classified into four groups as follows: 1) anti-aging, 2) physical strength and power, 3) healthy sex, and 4) relief from erectile dysfunction. The herbs that appears in Thai foods in everyday life with claimed medication results from the formulary textbooks were identified. They were 49 food ingredients from 143 herbs presented in 62 aphrodisiac formulas. The herbs with herbal aphrodisiac groups (1 and 2 and 3 and 4) were ranked by the number of times they appeared thusly; Pepper, Galingale (Finger root), Ginger, Long pepper, and Nutmeg. The paper correlates the herbal foods traditionally used aphrodisiacs with recent scientific validation for the management of sexual health.